التدقيق المحاسبي كآلية لتفعيل الرقابة الجبائية -دراسة حالة بمديرية الضرائب لولاية المسيلة- - جميات مديحة; - جميات لبنى (جامعة المسيلة, 2024)
تهدف هذه الدراسة إلى التعرف على أسس التدقيق المحاسبي وأهم معاييره، ومدى مساهمته في تفعيل الرقابة الجبائية، والذي يتم من خلاله الكشف عن التلاعبات والتصريحات الخاطئة للمكلفين بالضريبة، ويعتبر أحد الوسائل الرئيسية التي تستخدمها الإدارة الجبائية لمكافحة التهرب الضريبي وتفعيل الرقابة الجبائية، ومن أجل الوقوف على هذه المساهمة تم إجراء دراسة حالة على مستوى مديرية الضرائب لولاية المسيلة، وتم التوصل إلى أن الإدارة الجبائية تعتمد على تحقيقات ثلاث في مجال التدقيق المحاسبي وهذه التحقيقات المتمثلة في التحقيق المحاسبي والتحقيق المصوب والتحقيق في مجمل الوضعية الجبائية تلعب دورا هاما في تفعيل الرقابة الجبائية من خلال كشف مختلف حالات الغش والتهرب الضريبي والتصريحات الخاطئة. This study aims to identify accounting auditing as a mechanism for activating fiscal control Through the fiscal administration's action to reduce the phenomenon of tax evasion by means of various forms of fiscal control, Through which sincere and correct statements were obtained from the taxpayers in addition to disclosing the manipulations and accounting audit is one of the main means used by the fiscal administration to combat tax evasion, The audit also contributes to activating fiscal control by detecting irregularities and errors. For its part, this study was carried out at the level of the Tax Directorate of the State of Mselle, where one of the files of the controlled tax officials was examined for the accounting investigation, the corrected investigation and the investigation of the entire fiscal situation.
Keywords: التدقيق المحاسبي، الرقابة الجبائية، مديرية الضرائب لولاية المسيلة.; Audit comptable :contrôle fiscal; Direction des impôts de M'sila.